Pengaruh Capital Adequacy Ratio (CAR), Beban Operasional Pendapatan Operasional (BOPO), Return on Asset (ROA) dan Net Interest Margin (NIM) terhadap Financing Deposit Ratio (FRD) di PT. BPRS Bhakti Sumekar Sumenep (Periode 2011-2015) - Cholida Noerainon; Sri Handayani (Institut Agama Islam Negeri Madura, 2016)
The Bank is an industry whose business activities relying on public confidence so that the health of banks is done by maintaining the quality so that the bank can meet its obligations and maintain its performance. The purpose bank will be realized if the bank is able to significantly improve their performance optimal. To be able to function properly, the banks should have enough capital, maintaining its asset quality with a good, well-managed and operated by the precautionary principle thus generate enough profit to maintain the continuity of its business and maintain its liquidity so that it can meet its obligations at any time. the purpose of this study is the first: To determine the effect of the Capital Adequacy Ratio (CAR), Operating Expenses Towards Operating Income (OEOI), Return on Assets (ROA) and Net Interest Margin (NIM) simultaneously to the Financial to Deposit Ratio (FDR) PT. BPRS Bhakti Sumekar Sumenep. Second: To determine the effect of the Capital Adequacy Ratio (CAR), Operating Expenses Towards Operating Income (OEOI), Return on Assets (ROA) and Net Interest Margin (NIM) partially on Financial to Deposit Ratio (FDR) PT. BPRS Bhakti Sumekar Sumenep. Third: To determine which variables are the most dominant influencing on Financial to Deposit Ratio (FDR) at PT. BPRS Bhakti Sumekar Sumenep. In this research uses quantitative methods with the technique of multiple linear regression analysis with the help of SPSS analysis tools, while proving the hypothesis using a calculation T test and F test. The data used is secondary data namely quarterly publication report documentation results. The research results shows that the variables CAR, OEOI, ROA and NIM simultaneously no effect towards FDR PT. BPRS Bhakti Sumekar Sumenep because Sig. > 0.05 and the value of Fcount <Ftable. After removing several independent variables are considered to cause occurred multikolinearitas in this research i.e. the variable OEOI and ROA, then the variable CAR and NIM simultaneously positive effect is not significant to FDR for Sig. <0.05 with a value of Fcount > Ftable (6.032> 4.41). The variable CAR, OEOI, ROA and NIM partially no effect on FDR PT. BPRS Bhakti Sumekar Sumenep as a result Sig. > 0.05 and tcount <ttable. Variable CAR is not a variable that is most dominant influencing to FDR PT. BPRS Bhakti Sumekar Sumenep as a result Sig. > 0.05